Extreme cold events in Europe under a reduced AMOC - Meccia V. L.; Simolo C.; Bellomo K.; Corti S. (Environmental Research Letters, 2024)
There is a consensus that a weakened Atlantic Meridional Overturning Circulation (AMOC) decreases mean surface temperature in the Northern Hemisphere, both over the ocean and the continents. However, the impacts of a reduced AMOC on cold extreme events have not yet been examined. We analyse the impacts of a reduced AMOC strength on extreme cold events over Europe using targeted sensitivity experiments with the EC-Earth3 climate model. Starting from a fully coupled ocean-atmosphere simulation in which the AMOC was artificially reduced, a set of atmosphere-only integrations with prescribed sea surface temperature and sea-ice cover was conducted to evaluate the effects of weakly and strongly reduced AMOC strength. Despite overall cooling, reduced AMOC leads to fewer winter cold spells in Europe. We find that the weakened AMOC intensifies near-surface meridional gradient temperature in the North Atlantic and Europe, thus providing the energy to boost the jet stream. A stronger jet stream leads to less atmospheric blocking, reducing the frequency of cold spells over Europe. Although limited to the output of one model, our results indicate that a reduced AMOC strength may play a role in shaping future climate change cold spells by modulating the strength of the jet stream and the frequency of atmospheric blocking.